Association between breakfast patterns and executive function among adolescents in Shanghai, China - Wang, Xuelai; Qu, Shuangxiao; Yang, Dongling; Qi, Wenjuan; Zhang, Fengyun; Zhu, Rong; Sun, Lijing; Yan, Qiong; Qi, Yue; Yue, Guizhen; Yin, Cancan; Luo, Chunyan (Frontiers in Nutrition, 2024)
Introduction The aim of this cross-sectional study was to investigate the association between breakfast patterns and executive function among adolescents in Shanghai, China. Methods In 2022, we randomly recruited 3,012 adolescents aged 12–13 years from all administrative districts in Shanghai. Breakfast information was collected by parents using a one-day recall method. Executive function was measured using the Behavior Rating Inventory of Executive Function-Parent Version. Latent Class Analysis was performed to identify breakfast patterns based on the food groups in the Diet Quality Questionnaire for China. Results Breakfast patterns were classified into three categories: “Egg and milk foods”, “Grain foods”, and “Abundant foods”, except for adolescents who skipped breakfast. Logistic regression was used to estimate the multivariate odds ratio (ORs) and 95% confidence intervals (95% CI) for the association between breakfast patterns and potential executive dysfunction. Adolescents in the “Abundant foods” class had a lower risk of executive dysfunction in terms of initiate (OR: 0.36; 95% CI: 0.17–0.76), and organization of materials (OR: 0.18; 95% CI: 0.04–0.94), compared to those who skipped breakfast. Similarly, the breakfast patterns of “Grain foods” and “Egg and milk foods” were associated with a lower risk of executive dysfunction, including initiate and working memory. Discussion Our findings suggest that breakfast patterns were associated with executive function. The improvement of breakfast patterns among adolescents should be a significant public health intervention.